2009
DOI: 10.1097/mph.0b013e31818e532c
|View full text |Cite
|
Sign up to set email alerts
|

Minimal Residual Disease in Peripheral Blood Stem Cell Harvests From High-risk Neuroblastoma Patients

Abstract: The correlation between an unfavorable outcome and high TH expression in patients' PBSC harvests was not significant. This indicates a need to increase sample size in a long-term clinical outcome study to clarify the importance of TH mRNA contamination in PBSC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 23 publications
1
12
1
Order By: Relevance
“…On this new cohort, the persistence of MRD detected with RQ-PCR in PBSC predicts poorer overall survival (OS) in patients with HR-NB regardless of whether or not PBSC were re-injected or purged (P ¼ 0.04). Our findings are in line with Avigad et al [4], who demonstrated that patients harboring TH expression had reduced progression-free survival, and Corrias et al [5], who showed borderline negative effect of positive MRD on event-free survival (EFS) in patients rescued in CR (Table II). However, other studies showed no significant difference in OS between patients with positive or negative MRD in PBSC [1,5].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…On this new cohort, the persistence of MRD detected with RQ-PCR in PBSC predicts poorer overall survival (OS) in patients with HR-NB regardless of whether or not PBSC were re-injected or purged (P ¼ 0.04). Our findings are in line with Avigad et al [4], who demonstrated that patients harboring TH expression had reduced progression-free survival, and Corrias et al [5], who showed borderline negative effect of positive MRD on event-free survival (EFS) in patients rescued in CR (Table II). However, other studies showed no significant difference in OS between patients with positive or negative MRD in PBSC [1,5].…”
Section: Discussionsupporting
confidence: 92%
“…However, reports on the impact of MRD in PBSC are conflicting. Avigad et al [4] and Corrias et al [5] showed no correlation between MRD in PBSC and unfavorable outcome, while our previous studies suggested that positive MRD in PBSC was a poor prognostic factor [2,6]. Moreover, as MRD status in PBSC reflects pre-harvest bone marrow (BM) status, some authors have suggested that positive MRD in the BM shortly before PBSC collection might be a valuable predictive tool [7,8].…”
Section: Introductionmentioning
confidence: 88%
“…Most previous studies of molecular MRD in patients with HR‐NB using qRT‐PCR for NB mRNA markers were performed at early time points during the disease and treatment course . Only a few patients were followed up with qRT‐PCR for longer periods.…”
Section: Discussionmentioning
confidence: 99%
“…Most previous studies of molecular MRD in patients with HR-NB using qRT-PCR for NB mRNA markers were performed at early time points during the disease and treatment course. [1][2][3][4][5][6][7][8][9] Only a few patients were followed up with qRT-PCR for longer periods. Two patients with HR-NB were monitored for 61 and 67 weeks, 10 and we previously reported one patient with HR-NB followed up for 157 weeks after diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation